2018
DOI: 10.1371/journal.pone.0196048
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells from human umbilical cord prevent the development of lung fibrosis in immunocompetent mice

Abstract: Lung fibrosis is a severe condition resulting from several interstial lung diseases (ILD) with different etiologies. Current therapy of ILD, especially those associated with connective tissue diseases, is rather limited and new anti-fibrotic strategies are needed. In this study, we investigated the anti-fibrotic activity in vivo of human mesenchymal stromal cells obtained from whole umbilical cord (hUC-MSC). Adult immunocompetent C57BL/6 mice (n. = 8 for each experimental condition) were injected intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Among these cells, MSCs are a subset of multipotent cells, which may be identified in a large variety of tissues, including bone marrow, placenta, umbilical cord, adipose tissue, teeth and menstrual fluid, largely involved in the reparative function after damage, thus suggesting their potential role in regenerative medicine 1418 . Considering the pleiotropic effects of MSC, displaying immunomodulatory, angiogenic and antifibrotic capabilities, MSC-based therapy could counteract the three main pathogenic axes of SSc 1719 . On these bases, MSCs isolated from SSc patients (SSc-MSCs) were largely studied and it is largely accepted that SSc-BM-MSCs strongly differentiate toward myofibroblasts, mainly after cross-talking with endothelial cells from SSc patients, thus confirming the link between the early vascular involvement of SSc and subsequent fibrosis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these cells, MSCs are a subset of multipotent cells, which may be identified in a large variety of tissues, including bone marrow, placenta, umbilical cord, adipose tissue, teeth and menstrual fluid, largely involved in the reparative function after damage, thus suggesting their potential role in regenerative medicine 1418 . Considering the pleiotropic effects of MSC, displaying immunomodulatory, angiogenic and antifibrotic capabilities, MSC-based therapy could counteract the three main pathogenic axes of SSc 1719 . On these bases, MSCs isolated from SSc patients (SSc-MSCs) were largely studied and it is largely accepted that SSc-BM-MSCs strongly differentiate toward myofibroblasts, mainly after cross-talking with endothelial cells from SSc patients, thus confirming the link between the early vascular involvement of SSc and subsequent fibrosis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Since cord blood-derived CD34 cells have been shown to differentiate into megakaryocytes with high efficiency compared with those isolated from peripheral blood and BM, we focused on identifying a compatible stromal cell from human UC tissue (23). Previous studies have identified MSC-like cells in human UC tissue, but the cells were not well defined (16)(17)(18)(19)(20)(21). Unlike previously isolated UC tissue stromal cells, which have been primarily derived from Wharton's jelly (17)(18)(19)21), we focused on isolating arterial-derived stromal cells since perivascular cells around arteries have been shown to regulate hematopoietic cell production during development (24).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that human BM MSCs (bMSCs), defined by their adherence to tissue culture plates, can improve platelet formation in vitro, although the nature of the cells was not well defined (15). Human umbilical cord (UC) tissue, has also been shown to harbor MSCs, although these cells have not been thoroughly characterized (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can differentiate into several types of cells including endothelial cells, myocytes, keratinocytes, and fibroblasts . Moreover, stem cells produce several anti‐inflammatory and antifibrotic mediators, and secrete factors that create a regenerative microenvironment . Cord blood stem cells embedded in a scaffold secrete for example MMP‐9, mediating collagen degradation in uterine scars, which improves the regeneration of the endometrium, myometrium and blood vessels .…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticmentioning
confidence: 99%
“…[127][128][129] Moreover, stem cells produce several anti-inflammatory and antifibrotic mediators, and secrete factors that create a regenerative microenvironment. [130][131][132][133] Cord blood stem cells embedded in a scaffold secrete for example MMP-9, mediating collagen degradation in uterine scars, which improves the regeneration of the endometrium, myometrium and blood vessels. 134 Administered cord blood stem cells also promote the recruitment of endogenous stem cells.…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeutmentioning
confidence: 99%